Role of the platelet-lymphocyte ratio as a prognostic indicator in patients with intracranial hemorrhage: A systematic review and meta-analysis - Xiang Yuan; Sen Zhang; Jun Wan; Jingxian Yang; Yongjie Deng; Yuning Feng; Qingyu Bao; Xin Liu; Yihong Shen; Xian Chen; Jingyao Zeng; Yu Zhang (PLoS ONE, 2025)
Background The prognostic value of platelet-lymphocyte ratio (PLR) in ischemic stroke had been investigated in previous studies. However, the results of studies on PLR in patients with intracranial hemorrhage (ICH) are inconsistent. We aimed to conduct a meta-analysis to determine the prognostic value of PLR in predicting functional outcome and mortality in patients with ICH. Methods We searched the databases of PubMed, Embase, the Cochrane Library, and CNKI for relevant studies up to 10th June 2024. The Newcastle Ottawa Quality Assessment Scale (NOS) was applied to evaluate the quality of the included studies. We calculated the pooled odds ratios (OR) with 95% confidence intervals (CI) between PLR and both functional outcome (as measured by the modified Rankin Scale, mRS) as well as mortality. Poor functional outcomes were defined as mRS > 2. Results A total of 6 studies with 2992 patients were included. The random effects meta-analysis demonstrated that elevated PLR exhibited an association with poor functional outcome in patients with ICH (OR = 1.69; 95% CI [1.39–2.07]; P<0.0001; I2 = 24%). Similarly, elevated PLR was associated with mortality in patients with ICH (OR = 1.65; 95% CI [1.12–2.43]; P = 0.01; I2 = 31%). Conclusion This study suggested that elevated PLR was significantly associated with poor functional outcome (mRS>2) and increased mortality, indicating that elevated PLR could serve as a reliable a prognostic factor for unfavorable clinical outcomes in patients with ICH. It is advisable to conduct extensive prospective investigations across diverse ethnic backgrounds to verify the accuracy of this correlation prior to its utilization in clinical settings.